Características da degeneração macular relacionada à idade, forma exsudativa, em pacientes brasileiros - Frederico Braga Pereira (2014)
Purpose: To report clinical, angiographic and tomographic features of neovascular age-related macular degeneration (AMD) in Brazilian. Methods: Data were collected from patients with newly diagnosed neovascular AMD. Clinical examination, color and red-free photographs, fluorescein angiography (FA), indocyanine green (ICG) angiogram, and spectral domain optical coherence tomography (OCT) were performed. Eyes were classified as having typical neovascular AMD, polypoidal choroidal vasculopathy (PCV), or retinal angiomatous proliferation (RAP). Results: Two hundred sixty-five eyes of 207 patients were included: 166 (62.6%) eyes had typical neovascular AMD, 65 (24.5%) eyes had PCV, and 34 (12.8%) eyes had RAP. Female patients had a slight predominance (54.6%); RAP had a higher percentage of bilateral active cases, compared to typical neovascular AMD (p = 0.015). The overall mean age was 73.7 years; 113 (54.6%) patients presented arterial hypertension; and 56 (27%) patients were smokers or former smokers. The overall mean visual acuity was 0.71 logMAR (logarithm of the minimum angle of resolution). Most (57.7%) patients were phakic. Regarding OCT data, 32 (12.1%) eyes had serous retinal pigment epithelial detachment (PED) and 214 (80.7%) eyes had fibrovascular PED; the mean foveal subfield macular thickness was significantly lower in eyes with PCV than in eyes with typical neovascular AMD and RAP (p < 0.001). Typical neovascular AMD had a higher percentage of predominantly classic and minimally classic lesions on FA, compared to PCV (p = 0.005). Conclusions: In Brazilian patients PCV and RAP represent 24.5% and 12.8%, respectively, of newly diagnosed neovascular AMD cases. Neovascular AMD subtypes have different FA presentation as well as different mean foveal macular thickness.